Identification of chemical warfare agents from vapor samples using a field-portable capillary gas chromatography/membrane-interfaced electron ionization quadrupole mass spectrometry instrument with Tri-Bed concentrator - Nagashima, Hisayuki; Kondo, Tomohide; Nagoya, Tomoki; Ikeda, Toru; Kurimata, Naoko; Unoke, Shohei; Seto, Yasuo (Journal of Chromatography A, 2015)
•Performance of portable gas chromatograph–mass spectrometer, Hapsite ER was evaluated.•Vapor form of fifteen chemical warfare agents were identified within 12min.•Quantification performance of thirteen agents except for L1 and CS were ascertained.•Carry-over, micro-concentration time effect and gasoline interference were examined.•Haspite ER is expected to be useful for field confirmation for chemical warfare agents. A field-portable gas chromatograph–mass spectrometer (Hapsite ER system) was evaluated for the detection of chemical warfare agents (CWAs) in the vapor phase. The system consisted of Tri-Bed concentrator gas sampler (trapping time: 3s−1min), a nonpolar low thermal-mass capillary gas chromatography column capable of raising temperatures up to 200°C, a hydrophobic membrane-interfaced electron ionization quadrupole mass spectrometer evacuated by a non-evaporative getter pump for data acquisition, and a personal computer for data analysis. Sample vapors containing as little as 22μg sarin (GB), 100μg soman (GD), 210μg tabun (GA), 55μg cyclohexylsarin (GF), 4.8μg sulfur mustard, 390μg nitrogen mustard 1, 140μg of nitrogen mustard 2, 130μg nitrogen mustard 3, 120μg of 2-chloroacetophenone and 990μg of chloropicrin per cubic meter could be confirmed after Tri-Bed micro-concentration (for 1min) and automated AMDIS search within 12min. Using manual deconvolution by background subtraction of neighboring regions on the extracted ion chromatograms, the above-mentioned CWAs could be confirmed at lower concentration levels. The memory effects were also examined and we found that blister agents showed significantly more carry-over than nerve agents. Gasoline vapor was found to interfere with the detection of GB and GD, raising the concentration limits for confirmation in the presence of gasoline by both AMDIS search and manual deconvolution; however, GA and GF were not subject to interference by gasoline. Lewisite 1, and o-chlorobenzylidene malononitrile could also be confirmed by gas chromatography, but it was hard to quantify them. Vapors of phosgene, chlorine, and cyanogen chloride could be confirmed by direct mass spectrometric detection at concentration levels higher than 2, 140, and 10mg/m3 respectively, by bypassing the micro-concentration trap and gas chromatographic separation.